PERAN PEMERINTAH DALAM MEMBANGUN EKONOMI SYARIAH DI INDONESIA - Husnul Khotimah Sylvia (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2019)
The role of the Government in developing and developing Islamic economics in Indonesia has a very urgent and important role capacity, because the determining factor for the sustainability of sharia economic development is the urgency of the government's role in several aspects; (1) The policy aspect ofunderstanding the role of government according to Islam, (2) the basic aspects of Islamic economic policy, (3) the policy aspects of understanding the Islamiceconomic system, (4) the policy aspects of fulfilling the law, (5) the policy aspects of governance execution and development. If the five aspects can be fulfilled and carried out, then it is assured that Indonesia will experience overall economic growth, all levels of society will increase and there will be no imbalanced economic inequality.